Interpretasi Al-Qur’an tentang Pedofilia Perspektif Tafsir Al-Azhar Karya Buya Hamka - Auwalul Makhfudhoh; Abu Bakar (Jurnal Studi Al-Qur'an, 2025)
In social life, humans cannot be separated from communication between others. In human consciousness as social beings, there is a need to share a sense of responsibility and nurture younger individuals from older individuals. One of the social problems that often occurs is social crimes against children (pedophilia). The reason why someone becomes a pedophile is because they have a traumatic past, cannot socialize, feel low self-esteem, economic factors, etc. The Qur'an describes this sexual disorder. The Qur'an describes this sexual disorder as an abominable act in Qs. An-Naml [27]:54 and Surah Al-An'am [6]:151 in the book of Al-Azhar interpretation by Prof. Dr. Hj Abdul Malik Abdulkarim Amrullah, also known as Buya Hamka. This heinous act is a disease; in addition to homosexuality, there is another explanation of sexual abnormalities, namely the sexual desire of older people attracted to younger ones. The results showed that this heinous act is found in the Qur'an story.